2019
DOI: 10.1038/s41419-018-1266-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of TNFα-TNFR1 and TNFα-TNFR2 in the differentiation and function of CD4+Foxp3+ induced Treg cells in vitro and in vivo periphery in autoimmune diseases

Abstract: Tumor Necrosis Factor (TNF) α is a multifunctional cytokine with pro-inflammatory and anti-inflammatory characteristics. Increasing evidence suggests that thymus-derived, natural regulatory T cells (nTreg) express a remarkably high level of TNF Receptor 2 (TNFR2) and TNFα modulates the number or function of nTreg via TNFR2 in autoimmune diseases. Nonetheless, Treg cells consist of at least nTreg and iTreg that are induced in the periphery or in vitro and two subsets may have different biological characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 40 publications
1
77
0
Order By: Relevance
“…In contrast, TNFR1 deficiency resulted in reduced differentiation of inflammatory T cells, while the iTregs function was unaltered. Using a colitis model, they confirmed that TNFR2 but not TNFR1 deficiency impaired iTreg functionality (Yang et al, 2019), and proposed that TNFR2 also plays a role of iTreg function.…”
Section: Non-infectious Diseasesmentioning
confidence: 83%
See 1 more Smart Citation
“…In contrast, TNFR1 deficiency resulted in reduced differentiation of inflammatory T cells, while the iTregs function was unaltered. Using a colitis model, they confirmed that TNFR2 but not TNFR1 deficiency impaired iTreg functionality (Yang et al, 2019), and proposed that TNFR2 also plays a role of iTreg function.…”
Section: Non-infectious Diseasesmentioning
confidence: 83%
“…Whereas, the function of TNFR2 for nTregs is wellcharacterized, less is known about the impact of TNFR2 on induced Tregs (iTreg). Recently, Yang et al (2019) demonstrated that TNFR2 deficiency impeded differentiation, proliferation, and function of iTregs. In contrast, TNFR1 deficiency resulted in reduced differentiation of inflammatory T cells, while the iTregs function was unaltered.…”
Section: Non-infectious Diseasesmentioning
confidence: 99%
“…Treg-mediated suppression serves as a vital mechanism for the negative regulation of immune-mediated inflammation, and it features prominently in autoimmune and inflammatory disorders. 36 , 37 , 38 Several lines of experimentation have provided the proof that a lack of Tregs is the cause of fatal autoimmunity. 39 , 40 , 41 , 42 CD8+ Tregs, one subset of Tregs, have been reported to display potent therapeutic effect in some diseases, such as lupus and GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Fuhrman et al found that CD226 was expressed in memory CD4 + T cells (Fuhrman et al, 2015). These abnormal cells and relative pro-inflammatory cytokines contribute to many immunologic diseases (Yang and Song Guo, 2016;Sujuan et al, 2018Sujuan et al, , 2019.…”
Section: Cd226 Participates In the Function Of Cd4 + T Cellsmentioning
confidence: 99%